1999
DOI: 10.1177/0193841x9902300601
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Decisions about Child Maltreatment

Abstract: To understand how decisions are made in abuse/neglect cases by the child welfare system, the authors asked child welfare experts and protective service line workers to make decisions about actual child abuse and neglect cases on the basis of written summaries of the cases. Respondents included 27 experts and 103 line workers. Regression analyses found that workers and experts emphasized the same case characteristics in making their decisions, but the decisions were not well structured in the sense that they we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 2 publications
1
54
0
3
Order By: Relevance
“…Reliability issues with clinical decision-making became especially salient following research conducted in the late 1980s and 1990s that suggested that case decisions were highly dependent on which worker a family received and the larger institutional context in which the case was processed, and less dependent on the seemingly objective facts of the case (Stein and Rzepnicki 1983;Rossi et al 1999;Lindsey 1992). Further, research demonstrated little connection between the criteria CPS workers used to make a judgment and established risk factors related to re-abuse (Baird and Wagner 2000;Gambrill and Shlonsky 2001).…”
Section: Structuring Child Welfare Decisionsmentioning
confidence: 99%
“…Reliability issues with clinical decision-making became especially salient following research conducted in the late 1980s and 1990s that suggested that case decisions were highly dependent on which worker a family received and the larger institutional context in which the case was processed, and less dependent on the seemingly objective facts of the case (Stein and Rzepnicki 1983;Rossi et al 1999;Lindsey 1992). Further, research demonstrated little connection between the criteria CPS workers used to make a judgment and established risk factors related to re-abuse (Baird and Wagner 2000;Gambrill and Shlonsky 2001).…”
Section: Structuring Child Welfare Decisionsmentioning
confidence: 99%
“…For example, Rossi, Schuerman and Budde (1999) found that the characteristics of the case worker do not affect the placement decision (e.g. their background and work experience), and so excluding this variable from the analysis does not alter the results.…”
Section: Many Explanatory Variablesmentioning
confidence: 99%
“…Research done by Wood et al (2001) shows that the concept of QoL emerged in an attempt to recognise and understand the importance of the impact of health care interventions on people. Impact is defined as 'the effects of an intervention that can be attributed uniquely to it' (Rossi et al, 1999). An important tool to measure QoL is 'the World Health Organisation's Quality of Life Tool' (WHOQoL), using a quantitative approach (Yadav, 2010).…”
Section: Assessing the Impact Of The Cbr Programmementioning
confidence: 99%